How to improve language and memory - Gómez Marulanda, Francisco Joel (Rastros Rostros, 2012)
The following short paper presents partial results of research on language and memory that is being developed in the Universidad Cooperativa de Colombia at Bucaramanga since the second semester of 2011. Memory and language are two terms that cannot be conceived independently, without the first one we could not afford the registration of the surrounding world in our brain. Without the second one, any information trace would be a cosmic drift. Memory is a function of the brain and at the same time a phenomenon of the mind that allows the organism to encode, store, and retrieve information. Encoding, storing and reproducing information is a job that becomes viable through language and strategies that are developed with it
Keywords: Brain; feelings; memory; neurogenesis; repetition